Recurrent Hypoglycemia Increases Anxiety and Amygdala Norepinephrine Release During Subsequent Hypoglycemia - McNay, Ewan (Frontiers in Endocrinology, 2015)
Recurrent hypoglycemia (RH) is a common and debilitating side effect of therapy in patients with both type 1 and, increasingly, type 2 diabetes. Previous studies in rats have shown marked effects of RH on subsequent hippocampal behavioral, metabolic, and synaptic processes. In addition to impaired memory, patients experiencing RH report alterations in cognitive processes that include mood and anxiety, suggesting that RH may also affect amygdala function. We tested the impact of RH on amygdala function using an elevated plus-maze test of anxiety together with in vivo amygdala microdialysis for norepinephrine (NEp), a widely used marker of basolateral amygdala cognitive processes. In contrast to findings in the hippocampus and pre-frontal cortex, neither RH nor acute hypoglycemia alone significantly affected plus-maze performance or NEp release. However, animals tested when hypoglycemic who had previously experienced RH had elevated amygdala NEp during plus-maze testing, accompanied by increased anxiety (i.e. less time spent in the open arms of the plus-maze). The results show that RH has widespread effects on subsequent brain function, which vary by neural system.